Emergence of Mobile Colistin Resistance (mcr-8) in a Highly Successful Klebsiella pneumoniae Sequence Type 15 Clone from Clinical Infections in Bangladesh - Refath Farzana (American Society for Microbiology, 2020)
ABSTRACT The emergence of mobilized colistin resistance genes (mcr) has become a serious concern in clinical practice, compromising treatment options for life-threatening infections. In this study, colistin-resistant Klebsiella pneumoniae harboring mcr-8.1 was recovered from infected patients in the largest public hospital of Bangladesh, with a prevalence of 0.3% (3/1,097). We found mcr-8.1 in an identical highly stable multidrug-resistant IncFIB(pQil) plasmid of ∼113 kb, which belonged to an epidemiologically successful K. pneumoniae clone, ST15. The resistance mechanism was proven to be horizontally transferable, which incurred a fitness cost to the host. The core genome phylogeny suggested the clonal spread of mcr-8.1 in a Bangladeshi hospital. Core genome single-nucleotide polymorphisms among the mcr-8.1-positive K. pneumoniae isolates ranged from 23 to 110. It has been hypothesized that mcr-8.1 was inserted into IncFIB(pQil) with preexisting resistance loci, blaTEM-1b and blaCTX-M-15, by IS903B. Coincidentally, all resistance determinants in the plasmid [mcr-8.1, ampC, sul2, 1d-APH(6), APH(3′′)-Ib, blaTEM-1b, blaCTX-M-15] were bracketed by IS903B, demonstrating the possibility of intra- and interspecies and intra- and intergenus transposition of entire resistance loci. This is the first report of an mcr-like mechanism from human infections in Bangladesh. However, given the acquisition of mcr-8.1 by a sable conjugative plasmid in a successful high-risk clone of K. pneumoniae ST15, there is a serious risk of dissemination of mcr-8.1 in Bangladesh from 2017 onwards. IMPORTANCE There is a marked paucity in our understanding of the epidemiology of colistin-resistant bacterial pathogens in South Asia. A report by Davies and Walsh (Lancet Infect Dis 18:256–257, https://doi.org/10.1016/S1473-3099(18)30072-0, 2018) suggests the export of colistin from China to India, Vietnam, and South Korea in 2016 was approximately 1,000 tons and mainly used as a poultry feed additive. A few reports forecast that the prevalence of mcr in humans and livestock will increase in South Asia. Given the high prevalence of blaCTX-M-15 and blaNDM in India, Bangladesh, and Pakistan, colistin has become the invariable option for the management of serious infections, leading to the emergence of mcr-like mechanisms in South Asia. Systematic scrutiny of the prevalence and transmission of mcr variants in South Asia is vital to understanding the drivers of mcr genes and to initiate interventions to overcome colistin resistance.